Protección y Seguridad a los miembros Policiales en la Legislación Ecuatoriana - Cabrera Mendieta, Richard Alejandro (2022)
This thesis is entitled "Protection and Security of Police members in Ecuadorian Legislation", the present research topic found its birth and development interest in the conflictive scenario that a police member finds, when acting in a situation particular where a latent threat to a legal right is displayed, whether its own or another's, by an aggressor or person who violates the fundamental right of personal integrity, acts with intent and intention to harm this right mentioned above, hindering the compliance with its constitutional duty to provide citizen security and its responsibility with public order. The study that was carried out statistically shows the limitation that police members experience in the case of defending a fundamental right; being unable to act; since there is a legal vacuum in our Ecuadorian legislation regarding police actions; a non-existent permissibility that could save the life of a civilian involved, in evidence of the above, it is necessary to indicate that the violation of fundamental rights such as: right to life, to personal integrity are a consequence of the lack of police action, due to not being in the existing legal framework and in force in the regulatory bodies; These fundamental rights must be effectively protected by the Ecuadorian State, through inclusive policies and actions with the aim of safeguarding the personal integration of the individual, and thus provide security and legal protection to the police officer (his actions and procedures), and thus, avoid possible crimes that may be committed. The situation object of the present investigation, evidences the lack of typification and permissibility in the police act; to the fulfillment of its constitutional duty to protect and serve, and as a consequence we have a violation of rights that can end in a criminal act of injury or death in the worst case; It is well known that not acting against a crime is considered "omission" but how to act if the same competent regulations do not allow proceeding or acting? Faced with this conflict, it is necessary to limit the lack of classification and regulations in our Ecuadorian legal system; which, allows visualizing the existing limitation and the impediment of police action in defense of the legitimate personal integrity of a person; However, in this thesis, materials and methods were applied that allowed the development of the investigation, as well as interviews and surveys with legal professionals, results that served to propose the project of legal reform to the Comprehensive Criminal Organic Code, with the purpose to typify or delimit a legal figure that provides security and protection to the police member at the time of acting in defense of one's own or another's right for citizen security, thus giving a solution to this problem, so that fundamental rights can be guaranteed of all people